Identification and Isolation of Type II NKT Cell Subsets in Human Blood and Liver - Yang Zhou, Jordi; Werner, Jens M.; Glehr, Gunther; Geissler, Edward K.; Hutchinson, James A.; Kronenberg, Katharina (Frontiers in Immunology, 2022)
Background: Steatotic livers are more prone to rejection, but are often transplanted owing to the shortage of available organs. Type II NKT (T2NKT) cells are liver-resident lymphocytes that react to lipids presented by CD1d. The role of T2NKT cells in rejection of fatty liver transplants is unclear, partly because of a lack of T2NKT cell markers and their very low frequency in blood. Here, we quantify human T2NKT cells in blood and liver tissue by flow cytometry and provide a strategy for their enrichment and expansion. Methods: Human T2NKT cells were identified as CD3+ CD56+ CD161+ TCR-γꝽ- TCRVα7.2- and TCRVα24- cells. T2NKT cells were enriched from blood by sequential positive selection using CD56 and CD3 microbeads. These were subsequently FACS-sorted to purity then expanded in vitro for 3 weeks using anti-CD3/CD28 beads and TGF-ꞵ1. Results: The frequency of human T2NKT cells in blood was very low (0.8 ± 0.4% of CD3+ T cells) but they were a more abundant population in liver (6.3 ± 0.9%). Enriched T2NKT cells expressed the transcription factor PLZF. A novel subset of FoxP3+ T2NKT cells was discovered in blood and liver tissue. T2NKT cells were expanded in culture by 15- to 28-fold over 3 weeks, during which time they maintained expression of all identifying markers, including PLZF and FoxP3 (16.9 ± 3.6%). Conclusions: Our work defines new strategies for identifying and isolating T2NKT cells from human blood and liver tissue. We showed that this rare population can be expanded in vitro in order to obtain experimentally amenable cell numbers. Further, we identified a novel T2NKT cell subset that stably expresses FoxP3, which might play a role in regulating innate-like lymphocyte responses in steatotic liver transplants.